(untitled) (International Journal of Research in Pharmaceutical Sciences and Technology, 2026)
Orphan drugs are developed specifically to treat rare diseases that affect small patient populations. To encourage their development, regulatory agencies including the U.S. Food and Drug Administration (FDA) and the European Medicines Agency (EMA) grant Orphan Drug Designation, which confers incentives such as tax credits, grant funding, and extended market exclusivity. These frameworks often include expedited approval pathways, such as the FDA’s Fast Track and the EMA’s PRIME scheme, to accelerate the availability of promising therapies. Because patient numbers are limited, orphan drug clinical trials are typically smaller and may use alternative endpoints or adaptive designs. Additional incentives, including reduced regulatory fees and extended patent protection, further stimulate investment in this area. Active collaboration with patient advocacy organizations is also critical for identifying unmet clinical needs, designing patient-centric studies, and strengthening recruitment. Together, these regulatory and collaborative strategies are reshaping orphan drug development and improving timely access to innovative treatments for patients with rare and underserved conditions.